2012
DOI: 10.4269/ajtmh.2012.11-0512
|View full text |Cite
|
Sign up to set email alerts
|

Human African Trypanosomiasis in a Traveler: Diagnostic Pitfalls

Abstract: Abstract. An Israeli traveler returning from Tanzania presented with a relapsing febrile illness. A diagnosis of Trypanosoma brucei rhodesiense infection was established by blood smear after nearly a month. Blood polymerase chain reaction failed to provide an early diagnosis of human African trypanososmiasis. Recognition of suggestive signs should prompt physicians to perform repeated tests before ruling out human African trypanososmiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The number of reported HAT cases is probably an underestimate. Some cases were probably never diagnosed correctly in developed countries, where doctors are familiar neither with the clinical manifestations of HAT, nor with the limitations of the various diagnostic modalities available today [46] . Death in such cases was probably erroneously attributed to other causes.…”
Section: Discussionmentioning
confidence: 99%
“…The number of reported HAT cases is probably an underestimate. Some cases were probably never diagnosed correctly in developed countries, where doctors are familiar neither with the clinical manifestations of HAT, nor with the limitations of the various diagnostic modalities available today [46] . Death in such cases was probably erroneously attributed to other causes.…”
Section: Discussionmentioning
confidence: 99%
“…Among travelers returning from sub-Saharan Africa with a febrile illness, spotted fever rickettsiosis due to Rickettsia africae was a common cause, highlighting that a complete physical examination is needed to detect a necrotic eschar at the site of the tick bite (36). Fever with or without rash occurring soon after a safari trip to East Africa should lead to a prompt blood film for Trypanosoma brucei rhodesiense to facilitate rapid diagnosis and reduce the risks for neuroinvasion and death (37,38). Early referral of severely ill returned travelers to a clinician experienced in travel and tropical medicine may help mitigate the potential severe sequelae of these infections.…”
Section: Discussionmentioning
confidence: 99%
“…Elsen et al (1990) reported Glossina fuscipes fuscipes and G. morsitans submorsitans from southwestern Saudi Arabia. Meltzer et al (2012) in Israel reported T. brucei rhodesiense in a traveler returning from Tanzania with a relapsing febrile illness, and diagnosis was established by blood smear after nearly a month. Kong et al (2012) found that specificity of the 529 bp-LAMP assay was determined using the DNA samples of T. evansi, Plasmodium falciparum, Paragonimus westermani, Schistosoma japonicum, Fasciola hepatica and Angiostrongylus cantonensis, without cross-reactivity with DNA of any parasite.…”
Section: Review and Discussionmentioning
confidence: 99%